DIE AKTUALITÄT DES ERSTEN KOMMENTARS ZUM RÖMERBRIEF: ORIGENES AUSLEGUNG ZU RÖM 9,1-5 : (EINE ORTHODOXE PERSPEKTIVE) - Ioniță, Alexandru (Sacra scripta, 2012)
Much current NT scholarship holds that Paul’s vision regarding the future of Israel in Romans 9-11 has been neglected in the history of interpretation for too long. The modern reconsideration of a Pauline Israel Theology has consequently, and often with good reason, neglected the patristic commentaries on the topic.This article intends to reveal how strikingly relevant to our modern times is the first commentary on Romans written by Origen in the Jewish context of Palestinian Caesarea. After a short description of the sinuous history of his commentary and its recent academic reception, I intend to compare Origen’s interpretation of Romans 9,1-5 with the most current scientific interpretations from the Protestant realm. This comparison will demonstrate the necessity and contemporaneity of Origen’s point of view on the one hand, as well as the importance of reconsidering Origen’s exegesis within the Orthodox Church on the other.